The coaching needs of high performance female athletes within the coach-athlete dyad - Norman, L. (International Sport Coaching Journal, 2015)
Within the research literature there is little work that has examined how coaches (and coaching) can positively influence female athletes` continued participation and development in performance sport. One barrier that has been recently cited that prevents more women from progressing in sport is the inability of coaches to understand how to engage their female athletes. With this in mind, utilising a phenomenological approach, the current study focused on the coaching preferences of female athletes within the elite coach-athlete dyad. Through interviews with 27 current high performance female athletes, four major coaching needs were found. These were: to be supported as a person as well a performer, coaching to be a joint endeavour, the need for positive communication, and recognition of the salience of gender within the coach-athlete dyad. The findings highlight the complexities and contradictions that are inherent within such a relationship, but ultimately provide evidence that the relational expertise of coaches is at the forefront of these women`s coaching needs. The present study also demonstrates that gender is a salient influence on the coach-athlete relationship. Such findings hold practical significance through demonstrating the need for gender-responsive coaching practitioners.